Digital Health Revolution in Saudi Arabia: A Narrative Review of Healthcare Transformation - Mahmoud Abdel Hameed Shahin (Healthcare, 2026)
Digital transformation (DT) is a strategic priority for healthcare systems seeking to improve the quality of care, patient safety, and operational efficiency. In Saudi Arabia, DT is central to Vision 2030; however, evidence regarding its effects on healthcare quality and safety remains dispersed across technologies and healthcare settings. This narrative review aimed to examine the impact of digital transformation on healthcare quality and patient safety in Saudi Arabia and to identify the principal implementation facilitators, barriers, and policy implications. A structured narrative literature search was conducted for publications from January 2010 to March 2026 using PubMed/MEDLINE, Scopus, Web of Science, Google Scholar, the Saudi Digital Library, and relevant Saudi governmental and policy documents. In total, 64 peer-reviewed studies, reviews, reports, and policy documents addressing digital health initiatives and outcomes related to quality, safety, efficiency, or patient experience were included. Evidence was synthesized thematically, focusing on electronic health records, digital prescribing, online appointment systems, clinical and pharmacy automation, claims and financial analytics, telemedicine, governance, and workforce factors. The reviewed evidence indicates that Electronic Health Record (EHRs), computerized provider order entry, e-prescribing, barcode-supported medication systems, telemedicine, digital appointment platforms, and automated workflows can improve access to care, documentation, care coordination, medication safety, workflow efficiency, and patient experience. However, the benefits of DT are constrained by fragmented infrastructure, limited interoperability, workforce resistance, insufficient digital literacy, funding limitations, and unclear or fragmented governance and regulatory arrangements. In conclusion, digital transformation has substantial potential to enhance healthcare quality and patient safety in Saudi Arabia. Achieving these benefits requires context-sensitive implementation, interoperable systems, strong governance, sustained investment in infrastructure and workforce capacity, and effective leadership and change-management strategies aligned with Vision 2030.